2020
DOI: 10.1101/2020.03.16.993949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IsOculudentavisa bird or even archosaur?

Abstract: Recent finding of a fossil – Oculudentavis khaungraae Xing et al. 2020, entombed in a Late Cretaceous amber – was claimed to represent a humming bird-sized dinosaur1. Regardless of the intriguing evolutionary hypotheses about the bauplan of Mesozoic dinosaurs (including birds) posited therein, this enigmatic animal demonstrates various morphologies resembling lizards. If Oculudentavis was a bird, it challenges several fundamental morphological differences between Lepidosauria and Archosauria. Here we reanalyze… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On 11 March 2020, a paper describing a specimen preserved in amber from Myanmar, thought to be a bird-like dinosaur, was published in Nature (37). The paper was retracted three months later, on 22 June 2020 after Nature launched an investigation following the publication of a preprint (now published in Vertebrata PalAsiatica) on the bioRxiv server by another group of palaeontologists who reanalysed the original computer tomography data and demonstrated that the specimen in fact showed lizard-like features (38). While the retraction itself was not the result of any apparent fraud (39), the publication of this study brought an important issue further into the spotlight: the controversies around Myanmar amber (also referred to as Burmese or Kachin amber), particularly its links to human rights abuses by the Myanmar military on ethnic minorities in the northern state of Kachin, where most amber from Myanmar is mined (40).…”
Section: Ethical and Legal Transgressions In Palaeontologymentioning
confidence: 99%
“…On 11 March 2020, a paper describing a specimen preserved in amber from Myanmar, thought to be a bird-like dinosaur, was published in Nature (37). The paper was retracted three months later, on 22 June 2020 after Nature launched an investigation following the publication of a preprint (now published in Vertebrata PalAsiatica) on the bioRxiv server by another group of palaeontologists who reanalysed the original computer tomography data and demonstrated that the specimen in fact showed lizard-like features (38). While the retraction itself was not the result of any apparent fraud (39), the publication of this study brought an important issue further into the spotlight: the controversies around Myanmar amber (also referred to as Burmese or Kachin amber), particularly its links to human rights abuses by the Myanmar military on ethnic minorities in the northern state of Kachin, where most amber from Myanmar is mined (40).…”
Section: Ethical and Legal Transgressions In Palaeontologymentioning
confidence: 99%
“…They considered it to be a "hummingbird-sized dinosaur" and referred it to the higher taxon 'Aves Linnaeus, 1758'. Shortly after, Li et al (2020), in an online unreviewed 'preprint' (which has so far remained 'unpublished' in a peerreviewed scientific periodical), provided arguments strongly suggesting that this ill-preserved specimen was not a bird, not even an archosaur, but most likely a lepidosaur and even a squamate.…”
Section: Preliminary Remindermentioning
confidence: 99%
“…In paleontology, because of the fragmentary nature of most fossils, the discovery of further specimens or a re-analysis of the original one may change the interpretation researchers had on the species within a few months. The views on the phylogenetic position of Oculudentavis has shifted rapidly, indeed, and rather radically, which sugggests that perhaps the first publication went too far and forced a position in Aves, being thus very 'interesting mediatically', despite elements which suggested a non-archosaurian allocation (Li et al 2020). But this was just an accelerated form of the widespread way paleontology works, often through zigzagging leaps.…”
Section: Nomenclatural Implicationsmentioning
confidence: 99%
“…The interpretation of HPG-15-3 as a lizard rather than a bird, has already been made (Xing et al, 2020a); one metanalysis discussed its phylogenetic placement using an ad hoc revision of diagnostic features of diapsid clades, but without testing the position of Oculodentavis in phylogenetic analysis (Li et al, 2020). In response, the original authors added Oculudentavis to a amniote data set (Pritchard and Nesbitt, 2017) and recovered Oculodentavis as well nested among a group of Enanthiornithes birds (O'Connor et al, 2020), arguing that placement of this taxon with squamates only occurs if all avian taxa are removed.…”
Section: Grs-ref-28627 Is a Secondmentioning
confidence: 99%